2018
DOI: 10.1093/mmy/myy003
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Histoplasma capsulatum var duboisii in baboons from archived formalin-fixed, paraffin embedded tissues

Abstract: Histoplasma capsulatum var. duboisii (Hcd) infections have been well documented to cause chronic granulomatous disease, mainly involving the skin of baboons and humans in African countries primarily. This retrospective study classified the subspecies of Histoplasma and developed a phylogenetic tree utilizing DNA sequences extracted from formalin-fixed, paraffin embedded (FFPE) tissues from 9 baboons from a research colony in Texas histologically diagnosed with Hcd. Based on sequence analysis of ITS-2, Tub-1, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, recent genetic studies challenge this classification and renders it phylogenetically insignificant. Findings from these studies show that the Histoplasma genus contains at least 4 phylogenetic species including an African species that contained capsulatum , duboisii , and farciminosum strains [ 92 96 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent genetic studies challenge this classification and renders it phylogenetically insignificant. Findings from these studies show that the Histoplasma genus contains at least 4 phylogenetic species including an African species that contained capsulatum , duboisii , and farciminosum strains [ 92 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Africa, high prevalence of equine histoplasmosis is commonly reported in Ethiopia [ 97 ]. Although human to animal or animal to animal transmission is not established, a recent case has been attributed to the occurrence of histoplasmosis caused by Hcd in a baboon in America due to the importation of baboons from Senegal [ 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, an African nation, equine histoplasmosis has been extensively reported [14]. A recent case of histoplasmosis associated with Hcd in a baboon in America has been related to the import of baboons from Senegal [15]. Still, there is lack of evidence for either human-to-human or animal-to-animal transmission.…”
Section: Epidemiologymentioning
confidence: 99%
“…The variety capsulatum causes classical histoplasmosis in humans, and its highest occurrence is in the Americas. The variety duboisii causes histoplasmosis in humans and non-human primates, particularly in Central and Western Africa [11,12], while the variety farciminosum causes granulomatous alterations or ulcerated lesions in the skin and mucous membranes of dogs in Japan [13], and epizootic lymphangitis in equids in Europe, Africa, and Asia [9,14]. Nowadays, phylogenetic studies have revealed extensive genetic diversity, and new phylogenetic species/lineages have been proposed in the Histoplasma complex [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of this disease for public health, it is not a notifiable disease; therefore, epidemiological data are scarce and the occurrence is underestimated in different Brazilian regions [26,[29][30][31]. In addition to human cases, histoplasmosis has been diagnosed in dogs [32], cats [33], equines [3], birds [8], and rabbits [4], while asymptomatic infection has been reported in bats, marsupials, rodents, xenarthras, and nonhuman primates [7,11,34,35].…”
Section: Introductionmentioning
confidence: 99%